Clear cell chondrosarcoma: Cytologic findings in six cases. Issue 9 (25th October 2013) - Jiang, Xiaoyin Sara; Pantanowitz, Liron; Bui, Marilyn M.; Esther, Robert; Budwit, Debra; Dodd, Leslie G.
<x xml:space="preserve">Abstract</x> Clear cell chondrosarcoma (CCCS) is a rare variant of chondrosarcoma characterized, in most instances, by indolent behavior and a long interval to progression of disease. CCCS commonly occurs in adult individuals and has a proclivity for the epiphysis of long bones, although it has been reported in other sites. This lesion is difficult to diagnose preoperatively. Factors contributing to difficulty in recognizing this lesion include its relative scarcity as well as its tendency to be confused with other lesions on imaging studies. In the following, we report six cases of CCCS initially diagnosed by fine needle aspiration and/or touch preparations of needle biopsy samples. The cytologic features identified include large, plasmacytoid cells with foamy cytoplasm as well as extracellular chondroid type matrix material. Definitive diagnosis was made in each case by recognizing the "clear cell" nature of the tumor on cell block material. Diagn. Cytopathol 2014;42:784–791. © 2013 Wiley Periodicals, Inc.